The use of euphemism in contemporary Islamic english texts - Fatimatuzzahraa Samsudin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study seeks to identify the euphemisms available in contemporary Islamic English texts, to discover the main euphemized themes in the texts, to assess how euphemisms are phrased to achieve the purpose in these texts and to examine whether the English euphemisms in the texts reflect the Islamic culture. This research gathered relevant data from 50 selected topic-based Islamic articles from two journals – The American Journal of Islamic Social Sciences and Intellectual Discourse. Two frameworks were developed to collect the data; the first is a framework devised by the present researcher to categorize euphemisms under their respective themes and the second is based on Warren's (1992) model of structural features of euphemisms, which focuses on the structure of euphemistic expressions and processes of word formation. The findings indicate that first, there are eight main distinct themes of euphemism, namely death and the afterlife; societal matters; sexual morality and behaviours; women; religion; politics; economy; and one mixed theme dubbed as “others”, second, the structural features of euphemisms identified in the texts are compounding; single words; loan words; idiomatic expressions; metaphors and adjectival phrases and paraphrases, and third, the Islamic culture is somewhat reflected in some of the euphemisms, as the total number of Islam-based euphemistic expressions were 59 out of 170 euphemisms. The study also highlights the importance of contextuality in the study of euphemisms as context is very crucial in determining the meaning of euphemisms. The overall results show that there is evidence of euphemism in contemporary Islamic English texts, and demonstrate the success of the proposed analytical framework in achieving the objectives of this study. This study is significant for the reason that the corpus of the study was taken from Islamic articles, giving an extra luminosity to the study by casting light on English euphemisms derived and situated in an Islamic setting, thus amalgamating the English language with the Islamic culture. Future researches should incorporate a larger corpus of Islamic English texts to include not just Islamic academic writings but also Islamic literary creative writings (novels, poetry, etc.) and those circulated through the mass media (news articles, Islamic magazines, etc.), and more researches ought to be carried out on Islamic euphemisms found in spoken discourse, not just written.